If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(5 + -1(a + 1)) = 9 + -5(-1(2a + -3)) Reorder the terms: -1(5 + -1(1 + a)) = 9 + -5(-1(2a + -3)) -1(5 + (1 * -1 + a * -1)) = 9 + -5(-1(2a + -3)) -1(5 + (-1 + -1a)) = 9 + -5(-1(2a + -3)) Combine like terms: 5 + -1 = 4 -1(4 + -1a) = 9 + -5(-1(2a + -3)) (4 * -1 + -1a * -1) = 9 + -5(-1(2a + -3)) (-4 + 1a) = 9 + -5(-1(2a + -3)) Reorder the terms: -4 + 1a = 9 + -5(-1(-3 + 2a)) -4 + 1a = 9 + -5((-3 * -1 + 2a * -1)) -4 + 1a = 9 + -5((3 + -2a)) -4 + 1a = 9 + (3 * -5 + -2a * -5) -4 + 1a = 9 + (-15 + 10a) Combine like terms: 9 + -15 = -6 -4 + 1a = -6 + 10a Solving -4 + 1a = -6 + 10a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-10a' to each side of the equation. -4 + 1a + -10a = -6 + 10a + -10a Combine like terms: 1a + -10a = -9a -4 + -9a = -6 + 10a + -10a Combine like terms: 10a + -10a = 0 -4 + -9a = -6 + 0 -4 + -9a = -6 Add '4' to each side of the equation. -4 + 4 + -9a = -6 + 4 Combine like terms: -4 + 4 = 0 0 + -9a = -6 + 4 -9a = -6 + 4 Combine like terms: -6 + 4 = -2 -9a = -2 Divide each side by '-9'. a = 0.2222222222 Simplifying a = 0.2222222222
| 0=-2.625x^2+24.1x-9.95 | | 2(36+x)=13+x | | (3x-6)(2x-2)= | | (x+1)(x+2)=6(x+x+1)-12 | | (-4y^3+5-4y^2)-(6-6y^3)= | | y^2+8=-9y | | 1.1=x/20 | | y^2+8y+8=0 | | (-2p^4q^6)(3pq^3)= | | 4y+8=6y-6 | | m*m+3m-10= | | 2/3(6y-1)-8y=4/7(1-7y) | | m*m*3m-10= | | 5x^2-27=648 | | -2(a+b)=-2(b+a) | | 8x^2+14x= | | (256x^16)^1/4 | | k^6/k^3 | | 5x+3(6x-10)=16 | | 3x-24=132 | | 0=3x^2-16x-9 | | x^2(x^2-25)-16(x^2-25)=0 | | 1/3k-4=1 | | 3x^4-10x^3-5x^2-10x-8=0 | | (5.2+p)+2p=5.2+(p+2a) | | 0=3x^2-10x-7 | | (3x^2)(4x^4)= | | (-(-2y^3/^2)^4 | | -2x+2y=1 | | 60x^3-54x=0 | | 3(r-14)+7(r-12)=14 | | 3x-13x=50 |